International students’ career preparation (Comparative & International Education Series, 2021)
International students (ISs) are a significant and growing student group with unique needs for success. We use 2015–2019 National Survey of Student Engagement data that includes over 4,000 ISs from more than 450 U.S. institutions of higher education. We will describe ISs’ future career plans, how prepared they are in terms of career-related skills and abilities, and how internships and other career-preparation experiences relate to these skills and abilities. Findings indicate that ISs’ country of origin and participation in internships play an important role in understanding students’ confidence in the use of selected skills and abilities. Moreover, institutions need to find effective ways to balance ISs’ academic and social lives. We will provide detailed information about the IS landscape and the benefits that career services would bring to them, with implications for practice and future research that include finding effective ways to balance ISs’ academic and social lives.